2016
DOI: 10.1002/jbio.201500313
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive optical assessment of viscosity of middle ear effusions in otitis media

Abstract: Eustachian tube dysfunction can cause fluid to collect within the middle ear cavity and form a middle ear effusion (MEE). MEEs can persist for weeks or months and cause hearing loss as well as speech and learning delays in young children. The ability of a physician to accurately identify and characterize the middle ear for signs of fluid and/or infection is crucial to provide the most appropriate treatment for the patient. Currently, middle ear infections are assessed with otoscopy, which provides limited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 36 publications
0
47
0
2
Order By: Relevance
“…The structural information of the LCI axial depth scans also add additional data for the diagnosis of the disease, such as the presence of a scattering middle ear effusion and/or biofilm. 4,6 In the design of the probe, the optimal overlap of the foci of the RS and LCI beams is required.…”
Section: System Design and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural information of the LCI axial depth scans also add additional data for the diagnosis of the disease, such as the presence of a scattering middle ear effusion and/or biofilm. 4,6 In the design of the probe, the optimal overlap of the foci of the RS and LCI beams is required.…”
Section: System Design and Experimental Setupmentioning
confidence: 99%
“…Recently, optical coherence tomography (OCT) and low-coherence interferometry (LCI) have emerged as enabling tools to provide physicians with more detailed three-dimensional (3-D) structural and biomechanical characteristics of the TM and any biofilm or effusion that may be present. [3][4][5][6] These advanced technologies not only improve the diagnostic sensitivity and specificity of OM but also provide additional and meaningful pathological information, such as the presence of a bacterial biofilm or effusion behind the TM and within the middle ear cavity. With both well-established approaches and these emerging technologies, our ability to assess middle ear infections has the potential to be improved considerably for otolaryngologists, primary care physicians, and pediatricians.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have used OCT in surgical settings, [13][14][15] although its use has previously been limited mainly to ex vivo [16][17][18][19] tissue due to technical challenges and physical limitations of light delivery to the ear. Our group has addressed many of these challenges and performed both animal 7,20 and human 6,[21][22][23][24][25] studies. Recently, one study 21 identified and visualized additional infection-related structures affixed to the TM in nearly every case of chronic OM, which led to our current interest to understand longitudinal changes in the observed structures following surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…OCT has been reported for the visualization of bacterial films behind the tympanic membrane [1] and for the visualization and assessment of effusions in the middle ear [2][3], which is important for the diagnosis of otitis media. Additionally, Doppler-OCT can be utilized for measuring the oscillation of the tympanic membrane during acoustical stimulation [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging the tympanic membrane through the human ear canal requires the adaption of OCT to a surgical microscope [6] or an ear speculum [3]. There, the field of view is limited to typically 3 mm due to the curved ear canal, which makes it difficult to image the entire tympanic membrane.…”
Section: Introductionmentioning
confidence: 99%